2015
DOI: 10.1128/aac.04214-14
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Resistance Studies with Bacteria That Exhibit Low Mutation Frequencies: Prediction of “Antimutant” Linezolid Concentrations Using a Mixed Inoculum Containing both Susceptible and Resistant Staphylococcus aureus

Abstract: Bacterial resistance studies using in vitro dynamic models are highly dependent on the starting inoculum that might or might not contain spontaneously resistant mutants (RMs). To delineate concentration-resistance relationships with linezolid-exposed Staphylococcus aureus, a mixed inoculum containing both susceptible cells and RMs was used. An RM selected after the 9th passage of the parent strain (MIC, 2 g/ml) on antibiotic-containing media (RM9; MIC, 8 g/ml) was chosen for the pharmacodynamic studies, becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 42 publications
0
16
1
Order By: Relevance
“…If evolutionary theory does not support the use of MPC as a general approach then why does this nevertheless appear to work in some cases [ 34 , 53 ]? The theory presented here provides some possible explanations.…”
Section: Discussionmentioning
confidence: 99%
“…If evolutionary theory does not support the use of MPC as a general approach then why does this nevertheless appear to work in some cases [ 34 , 53 ]? The theory presented here provides some possible explanations.…”
Section: Discussionmentioning
confidence: 99%
“…A similar approach using mixed bacterial populations to study resistance selection has been employed with E . coli [ 49 ], Streptococcus pneumoniae [ 50 52 ], Staphylococcus aureus [ 53 ] and Mycobacterium tuberculosis [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, recent work suggests that aggressive treatment strategies can hasten the emergence and spread of resistance [30][31][32][33][34][35][36][37][38][39][40][41]. In addition, numerous studies, both experimental and theoretical, provide evidence that less aggressive treatment strategies may be called for under some conditions [42][43][44][45][46][47][48][49][50], while several clinical trials have also demonstrated advantages of lower dose therapies [50][51][52][53][54][55][56][57][58].…”
Section: Introductionmentioning
confidence: 99%